Peringkat Sukuk Berdasarkan Return on Asset dan Debt to Equity Ratio - Amalia Cahyati; Nurnasrina Nurnasrina (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2019)
Purpose- This study is to examine the effect of return on assets (ROA) and debt to equity ratio (DER) on the rank of Sukuk listed on the Indonesia Stock Exchange (IDX). Methods- Data were collected by purposive sampling method with the number of companies sampled in the study were 7 companies with observations for 5 years. Findings- Results indicate that ROA and DER are proven to have a significant effect on Sukuk ratings. Implications- This study can be an evaluation for investors to determine investment decisions, especially Sukuk in Indonesia.